Relationship between biochemical and photosynthetic traits with asian soybean rust - Oliveira, Tássia B. de; Peixoto, Leonardo A.; Teodoro, Paulo E.; Alvarenga, Amauri A. de; Bhering, Leonardo L.; Hoffmann-Campo, Clara B. (Anais da Academia Brasileira de Ciências, 2018)
Asian soybean rust (Phakopsora pachyrhizi – ASR) is one of the major diseases that occur in soybean and causes great damage to commercial crops. Therefore, the goal of this work was to investigate the relationship between biochemical and photosyntetic parameters in soybean with ASR. Two experiments were performed in a randomized complete block with three treatments (water, Tween 20, and methyl jasmonate). The evaluated traits were: severity, chlorophyll pools, concentration of phenolic compounds content, enzyme activity, and photosyntetic parameters. Based on Pearson correlation, correlation network and path analysis it was verified that the severity had high correlation with almost all traits evaluated meanwhile photosynthesis is weakly related with almost all traits. Therefore, the occurrence of ASR affects directly the traits related to enzymatic activity and phenolic compounds content in soybean plants inoculated with ASR. The management of ASR is important to keep in normal levels the rates of photosynthesis carried out by the plant, and thus not affect the yield. Besides that, understanding the biochemical mechanisms and ecophysiological responses that occur during the soybean-P. pachyrhizi interaction has a great importance for breeding programs, as it will help for obtaining resistant cultivars or efficient methods in fungus control.
Keywords: Correlation network; Glycine max; Path analysis; Phakopsora pachyrhizi